Analysis of Students’ Scientific Process Skills Using the Discovery Learning Model on the Colligative Properties of Solutions - Fawziyah Sholihah Bayliz; Rizqy Nur Sholihat; Meyliana Wulandari (LPPM Universitas Negeri Jakarta, 2026)
Scientific process skills (SPS) are essential competencies that enable students to investigate phenomena, solve problems, and construct scientific understanding. Despite their importance, the development of SPS in chemistry learning remains challenging, particularly in topics that require conceptual understanding and practical investigation, such as colligative properties of solutions. This descriptive quantitative study assessed students’ scientific process skills during Discovery Learning-based instruction on colligative properties of solutions. The participants were 34 twelfth-grade students from SMA Negeri 14 Bekasi selected through purposive sampling. Data were collected using observation sheets completed by six observers and a 21-item student questionnaire. The data were analyzed using descriptive statistics to determine the level of SPS achievement across eleven skill indicators. The findings revealed that the average SPS score was 74.16% based on observations and 76.54% based on questionnaires, both categorized as good. Students demonstrated the strongest performance in using laboratory tools and materials, while predicting and hypothesis formulation showed comparatively lower achievement. These results suggest that Discovery Learning effectively supports the development of practical and inquiry-based scientific skills by actively engaging students in experimentation and concept discovery. However, higher-order SPS components, particularly prediction and hypothesis formulation, require additional instructional support. This study contributes empirical evidence on students’ SPS profiles in chemistry learning and highlights specific skill areas that should be strengthened to optimize Discovery Learning implementation in secondary education.